2008
DOI: 10.1007/s00259-008-1002-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of “non-acute” vascular prosthesis infection using 18F-FDG PET/CT: our experience with 96 prostheses

Abstract: PET/CT gave reliable results with an accuracy >95% in 75% of prostheses. PET/CT can identify those prostheses (25% of prosthesis) for which its diagnostic accuracy is diminished to 70-75%. In our series PET/CT was an excellent diagnostic modality for suspected VPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 29 publications
3
93
1
10
Order By: Relevance
“…In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ).…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ).…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
“…32 PET/CT alone or in combination with other imaging modalities can be considered if the results of standard CT studies are inconclusive for the diagnosis of VGI. [28][29][30][31][32][43][44][45][46] On the basis of the published studies, it is reasonable to use standard CT as the initial imaging modality for the diagnosis of VGI. [30][31][32] Intrathoracic VGI Imaging studies are necessary to confirm the diagnosis and define the extent of infection and vascular anatomy.…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, визуализирующие методы позво-ляют диагностировать развитие наиболее грозного ослож-нения течения инфекционного процесса -нарушение герметичности анастомоза с формированием ложной аневризмы и аррозивного кровотечения. В некоторых случаях, когда стандартные методы диагностики не по-зволяли однозначно судить о наличии или отсутствии ин-фекционного процесса в области СП, проводили пози-тронно-эмиссионную томографию (ПЭТ) с меченной фтором-18 фтор-2-дезокси-D-глюкозой (ФДГ) [13][14][15]. В ряде исследований было показано, что радиофармпре-парат ФДГ активно накапливается в тканях с высокой ме-таболической активностью, в том числе в воспалительном и инфекционном очагах [16].…”
Section: материал и методыunclassified
“…По мнению других авторов, ин-формативность КТ при ПИ не высока [16,18]. При обследовании 33 пациентов с подозрением на ПИ ФДГ-ПЭТ показала высокую чувствительность метода (91 %) [19,20], при этом прогностическая ценность достигла 95 % [21][22][23][24][25].…”
Section: таблиц аunclassified